Quorum sensing signals: aquaculture risk factor - Priya, P. Snega; Boopathi, Seenivasan; Murugan, Raghul; Haridevamuthu, B.; Arshad, Aziz; Arockiaraj, Jesu (Wiley, 2023)
Bacteria produce several virulence factors and cause massive mortality in fish and crustaceans. Abundant quorum sensing (QS) signals and high cell density are essentially required for the production of such virulence factors. Although several strategies have been developed to control aquatic pathogens through antibiotics and QS inhibition, the impact of pre-existing QS signals in the aquatic environment has been overlooked. QS signals cause detrimental effects on mammalian cells and induce cell death by interfering with multiple cellular pathways. Moreover, QS signals not only function as a messenger, but also annihilate the functions of the host immune system which implies that QS signals should be designated as a major virulence factor. Despite QS signals' role has been well documented in mammalian cells, their impact on aquatic organisms is still at the budding stage. However, many aquatic organisms produce enzymes that degrade and detoxify such QS signals. In addition, physical and chemical factors also determine the stability of the QS signals in the aqueous environment. The balance between QS signals and existing QS signals degrading factors essentially determines the disease progression in aquatic organisms. In this review, we highlight the impact of QS signals on aquatic organisms and further discussed potential alternative strategies to control disease progression.